Exploration of Ideas for Sustaining Digital Innovation Management : A Case Study in the Ostrobothnia Region of Finland - Dang, Duong; Mäkipää, Juho-Pekka; Mäenpää, Teemu; Pasanen, Tomi A. (Association for Information Systems, 2022)
Disruption of technologies, climate changes and epidemic crises have significantly affected individuals, organizations, and society. These phenomena force organizations to extend and innovate their business models to adapt to new circumstances. However, literature provides a limited coverage on how sustainable innovations ideas form and evaluate in practice. We thus focus on this issue in the present study. We used nominal focus group technique, C-K design theory for innovative design with citizen sciences as our study’s lenses. Data collection was from three groups of 81 participants who live in three cities in the Ostrobothnia region of Finland. The findings illustrate the process of establishing a sustainable innovation management idea and lesson learned on how to facilitate innovation groups in practice.
Keywords: case study; citizen science; Digital innovation; Finland; nominal focus group; transformation; fi=Tietotekniikka|en=Computer Science|